Physiological and yield parameters of wheat as affected by tiller removal and defoliation - Fioreze, Samuel Luiz; Borga, Iury; Ribeiro, Elisandra Cristina (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to evaluate the photosynthetic parameters, yield potential, and response to defoliation of wheat (Triticum aestivum) plants subjected to tiller removal. Two experiments were conducted under greenhouse conditions. In the first, the two following cultivars were evaluated for complete tiller removal: TBIO Audaz and BRS 394, with a high and low tillering capacity, respectively. In the second, only ’TBIO Audaz’ was subjected to detillering and defoliation at post-anthesis. Tiller removal increased the yield potential of the main stem of both tested cultivars and the CO2 assimilation potential of the flag leaf, which was possibly a strategy to meet the demands for an increased sink strength, as evidenced by the response curves to irradiance and leaf internal CO2 concentration. The partial defoliation of ’TBIO Audaz’ increased daily CO2 assimilation, both in intact and detillered plants. Detillered plants show a higher photosynthetic and yield potential of the main stem, but also a greater sensitivity to defoliation in the post-anthesis period.